Expression of MDR1, LRP, BCRP and BCL-2 genes at diagnosis of childhood ALL: comparison with mrd status after induction therapy - Fedasenka, U.U.; Shman, T.V.; Savitski, V.P.; Belevcev, M.V. (Experimental Oncology, 2008)
To investigate properties of leukemic cells by sorting out children diagnosed with ALL with different response to chemotherapy based on MRD level. Methods: We used a minimal residual disease (MRD) data on day 36 obtained with 3-colour flow cytometry as a reference. In view of MRD results, we used real-time PCR to assess expression levels of multidrug resistance associated genes MDR1, LRP and BCRP, antiapoptotic gene Bcl-2 in initial samples from children diagnosed with ALL. P-gp expression and function in initial samples were analyzed by flow cytometry. Results: Briefly, medians of relative expression levels of MDR1 gene were roughly comparable and in MRD+ group came to 22.8 (0.02–26.6; n = 9) vs 24.8 (3.9–41.4; n = 10) in MRD– group. Bcl-2 gene showed tendency to higher expression levels in MRD+ group with median at 5992.9 (521.0–10362.0; n = 9) compared to 3183.6 (1947.9–6581.0; n = 10) in MRD– group. LRP gene relative expression levels were similar in both groups and came to 1934.9 (1500.7–3490.4; n = 9) and 1408.5 (665.5–2917.1; n = 10) in MRD+ and MRD– groups, respectively. The median of BCRP expression levels in MRD+ group was considerably lower than that in MRD– group, namely 76000.0 (48196.2–169230.8; n = 9) and 227967.2 (16683.7–422222.2; n = 10), respectively, but statistical analysis showed no significant difference for this parameter. Conclusion: We investigated expression of multidrug resistance genes MDR1, LRP and BCRP and antiapoptotic gene Bcl-2 in leukemic cells at diagnosis, and MRD level at the end of induction therapy, and could not find obvious relations between these parameters. Цель: изучить свойства лейкозных клеток детей больных ОЛЛ с положительным и отрицательным результатом мониторинга минимальной резидуальной болезни после индукционной терапии. Методы: согласно результатам мониторинга минимальной резидуальной болезни (MRD) с помощью трехцветной проточной цитометрии на 36-й день больные были разделены на 2 группы: MRD– и MRD+. Для изучения уровней экспрессии генов MDR1, LRP, BCRP и BCL-2 в образцах костного мозга пациентов с диагнозом первичного ОЛЛ использовался метод относительной количественной ПЦР в режиме реального времени. Результаты: медианы уровней экспрессии гена MDR1 в изученных группах пациентов отличались незначительно и составили 22,8 (0,02–26,6; n = 9) в MRD+ и 24,8 (3,9–41,4; n = 10) в MRD–-группе. Тенденция к повышенной экспрессии гена BCL-2 выявлена в группе MRD+, где медиана составила 5992,9 (521,0–10362,0; n = 9), по сравнению с 3183,6 (1947,9–6581,0; n = 10) в группе MRD–. Относительная экспрессия гена LRP в изучаемых группах оказалась сходной, медианы составили 1934,9 (1500,7–3490,4; n = 9) и 1408,5 (665,5–2917,1; n = 10) в MRD+- и MRD–-группах соответственно. Медиана уровня экспрессии гена BCRP в группе MRD+ была значительно ниже таковой в группе MRD– — 76000,0 (48196,2–169230,8; n = 9) и 227967,2 (16683,7–422222,2; n = 10) соответственно, однако статистических анализ не подтвердил значимость различий. Выводы: при изучении уровней экспрессии генов MDR1, LRP, BCRP и BCL-2 в лейкозных клетках при установлении первичного диагноза ОЛЛ у детей и при мониторинге MRD после индукционной терапии не выявлена связь между данными параметрами.